Population Ethics and Different‐Number‐Based Imprecision. (22nd April 2016) - Arrhenius, Gustaf
Abstract: Recently, in his Rolf Schock Prize Lecture, Derek Parfit has suggested a novel way of avoiding the Repugnant Conclusion by introducing what he calls "imprecision" in value comparisons. He suggests that in a range of important cases, populations of different sizes are only imprecisely comparable. Parfit suggests that this feature of value comparisons opens up a way of avoiding the Repugnant Conclusion without implying other counterintuitive conclusions, and thus solves one of the major challenges in ethics. In this article, I try to clarify Parfit's proposal and evaluate whether it will help us with the paradoxes in population ethics.